Aspects of urinary tract infections and antimicrobial resistance in hospitalized urology patients in Asia: 10-Year results of the Global Prevalence Study of Infections in Urology (GPIU). Issue 4 (April 2018) - ,; Nikfallah, Abolghasem; Kassem, Adham Mohamad; Aljubory, Ahmed Khalil; Salman, Ahmed; Kutmanova, Ainura Zarylbekovna; Usupbaev, Akylbek Ch; Daud Natsheh, Ala Eddin; Andreychikov, Alexander Vladimirovich; Plekhanov, Alexei Yurievich; Vinokurov, Alexey Dmitrievich; Dolgiy, Alexey Alexeevitch; et al.
Abstract: Objectives: To assess Asian data from Global Prevalence Study on Infections in Urology (GPIU study) which has been performed more than 10 years. Methods: Seventeen Asian countries participated in the GPIU study between 2004 and 2013. Data for these countries were collected from the web-based GPIU database. The point prevalence of urinary tract infections (UTI) and antimicrobial susceptibility of representative pathogens were analysed for Asian geographic regions. Results: A total of 6706 patients (5271 male, 1435 female) were assessed during the study period, and 659 patients were diagnosed with a UTI (9.8%). Of these UTI patients, 436 were male and 223 were female. Mean patient age was 54.9 ± 19.3 years. Pyelonephritis and cystitis were the most common clinical diagnoses, representing 30.7% and 29.9% of patients, respectively. Escherichia coli was the most frequently identified uropathogen (38.7%). For the patients with urinary tract infection, cephalosporins were the most frequently used antibiotics (34.4%), followed by fluoroquinolones (24.1%), aminoglycosides (16.8%). Fluoroquinolone resistance was relatively high (ciprofloxacin 54.9%, levofloxacin 39.0%), and cephalosporin resistance 42% (42.5–49.4%). Of the antibiotics evaluated, uropathogens had maintained the highest level of susceptibility to amikacin and imipenem (24.9% and 11.3% resistance rates, respectively). Conclusion: Uropathogens in many Asian countries had high resistance to broad-spectrum antibiotics. Knowledge of regional and local resistance data and prudent use of antibiotics are important for proper management of UTI in Asian countries.